2005
DOI: 10.1177/001789690506400207
|View full text |Cite
|
Sign up to set email alerts
|

Fitness instructors: How does their knowledge on weight loss measure up?

Abstract: Objective To examine the knowledge, approaches and attitudes of fitness instructors dealing with clients seeking weight loss advice. Design A qualitative project whereby semi-structured interviews were conducted with ten fitness instructors representing a range of qualifications, work settings and years of experience. Setting Interviews were conducted at neutral sites identified by participants. Methods Interviews explored participants' knowledge on weight related issues including the etiology and consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Of concern is that those using the internet were also described as having difficulty discerning the credibility and quality of information sources [20]. The implication of educational level as a factor influencing choice of information sources is difficult to determine, given that there are little data on the educational qualifications of fitness trainers working with the public.…”
Section: Discussionmentioning
confidence: 99%
“…Of concern is that those using the internet were also described as having difficulty discerning the credibility and quality of information sources [20]. The implication of educational level as a factor influencing choice of information sources is difficult to determine, given that there are little data on the educational qualifications of fitness trainers working with the public.…”
Section: Discussionmentioning
confidence: 99%
“…For individual items, the ICC value and its 95% confidence interval (CI) are reported. An ICC value of 0.2-0.4 suggests poor agreement, 0.5-0.6 suggests moderate agreement, 0.7-0.8 suggests strong agreement and >0.8 suggests almost perfect agreement [19].…”
Section: Discussionmentioning
confidence: 99%
“…high-quality vs. low-quality). An additional strength was the examination of the test-retest reliability survey of the sources of practice knowledge items, which showed acceptable reliability [19].…”
Section: Original Researchmentioning
confidence: 99%
“…The literature reviewed underscored the importance of having a competent exercise instructor, as older exercisers attributed great value to having an instructor who was knowledgeable about exercise, as well as about gerontology. Herein, exercise participants acknowledged the instructor's role as competent practitioner, recognizing that certification was vital toward the assurance of technical proficiency, thus ensuring some degree of safe practice (Beaudreau, 2006;Brehm, 2004;Forsyth, Handcock, Rose, & Jenkins, 2005;Mehra et al 2016;Olsen, Telenius, Engedal, & Bergland, 2015;Taylor & Pescatello, 2016;Vseteckova et al, 2018). Moreover, Oldridge (1977) argued that instructors should teach safety techniques to exercisers in order to increase exerciser self-efficacy and further reduce the likelihood of injury.…”
Section: Competencementioning
confidence: 99%
“…In fact, Hawley, Skelton, Campbell, and Todd (2012) found that training was positively correlated with a favorable attitude toward older adults, and that certification, work experience, and work setting all influenced instructor attitude and perception of older adulthood. However, certification and/or gerontological competencies are not always required for employment in Canada (Forsyth et al, 2005;Kluge & Savis, 2001;Taylor & Johnson, 2008) despite the assertion that exercise instructor training for working with older adults requires more competence than training for working with younger adults (Ecclestone & Jones, 2004). Therefore, the role of competent instructor, which includes gerontological competence for older adult fitness, is not widely assured under current practices in Canada.…”
Section: Competencementioning
confidence: 99%